Pengaruh Kadar Perekat Terhadap Karakteristik Briket Arang Limbah Kayu Karet (Hevea brasiliensis Muell. Arg) - Rahmi Adi Bazenet; Wahyu Hidayat; Siti Mutiara Ridjayanti; Melya Riniarti; Irwan Sukri Banuwa; Agus Haryanto; Udin Hasanudin (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
The study aimed to determine the effects of adhesive content on rubber wood charcoal briquette characteristics. Wood charcoal was produced using a double-drum retort kiln at > 500°C.  Wood charcoals were crushed into powder and then mixed with tapioca adhesive of 5%, 10%, and 15%. The charcoal-adhesive mix was then pressed using a hydraulic press machine. For comparison, rubber wood biomass briquettes were also produced using wood particle-adhesive mix with similar adhesive content.  Biomass and charcoal briquettes characteristics as physical properties (density and water absorption), chemical properties (ultimate analysis, and FTIR analysis) and energy properties (calorific value) were evaluated.  The results showed that density ranged between 0.52-0.56 g/cm3, water absorption of 6.54-7.47%, C content of 82.67-84.41%, H content of 3.28-3.60%, N content of 0.67%-0.74%, and calorific value of 30.76-32.86 MJ/kg.  The results of FTIR analysis showed changes in the spectrum of the wave band on the functional groups OH, CH, C≡H, C=C, and C=O, indicating the decomposition of the chemical components of rubber wood due to pyrolysis.  The results prove that increasing the adhesive content can reduce the quality of briquettes.  Based on physical, chemical, and energy properties, charcoal briquettes with 5% adhesive showed better characteristics than briquettes with 10% and 15% adhesive content, showing water absorption of 6.54%, C content of 84.41%, H content of 3.28%, and heating value of 32.86 MJ/kg. Keywords:  adhesive content, charcoal briquette, pyrolysis, rubber wood waste, tapioca starch